Effects of childhood adversities on alexithymia features vary between sexes. Results of a prospective population study - Raimo K. R. Salokangas; Tiina From; Henri R. W. Salokangas; Lara Lehtoranta; Jaana Suvisaari; Seppo Koskinen; Jarmo Hietala; Matti Joukamaa; Max Karukivi (European Journal of Psychotraumatology, 2024)
Introduction: Adverse childhood experiences (ACEs) associate with various mental disorders, including personality features. Our understanding of how ACEs influence alexithymia features in the general population is limited. In a prospective population setting, we studied whether ACEs associate with alexithymia, and the role of sex and emotional symptoms in this association.Methods: In a Finnish population-based prospective study, 3,142 individuals aged between 30 and 64 years completed eleven ACE questions and the Toronto Alexithymia Scale in 2000 and 2011, and the Hopkins Symptoms Checklist in 2011. The effect of ACEs on alexithymia and its subdomains – difficulty identifying feelings (DIF), difficulty describing feelings (DDF), and externally oriented thinking (EOT) in 2000 and 2011 – was analysed using repeated measures ANOVA.Results: The number of ACEs and their main component, childhood social disadvantage, associated positively with total alexithymia scores and its subdomains DIF and DDF, and negatively with EOT. After controlling for the effect of depression and anxiety, the strength of these associations was reduced, but the effect of social disadvantage on DIF and EOT remained significant in females. Childhood family conflicts associated positively with DIF in males and negatively with EOT in females. Additionally, maternal mental problems associated positively with DIF and DDF in females.Discussion: In the general population, ACEs, particularly social disadvantage, are associated with adult alexithymia features. Alexithymia features, detectable from youth, may predispose individuals to emotional disturbances caused by childhood adversities. The effect of family conflicts and maternal mental problems on alexithymia features varies between sexes.